How to understand the parables of Jesus. A paradigm shift in parable exegesis - R. Zimmermann (Acta Theologica)
For many years, the exegesis of the parables of Jesus was determined by assumptions that were largely purported by Adolf Jülicher and subsequently underwent only insignificant modification. The Kompendium der Gleichnisse Jesu (ed. R. Zimmermann, Gütersloh 2007), whose methodology and hermeneutics are explained in this article, takes a new route, as can be illustrated in four steps. From a historical perspective, parable exegesis is released from its close relationship to the search for the Historical Jesus and is given new distinction by a paradigm of Jesus “remembered”. The customary religious-historical standardization of the parables (particularly with reference to rabbinical parables) is critically investigated from a traditio-historical perspective in order to again be able to highly value the extraordinary position of Jesus’ parables. From the perspective of the literary form of the parables, all internal differentiation must be made invalid by the New Testament text record itself. Instead, the discussion of a comprehensive genre of “parable” utilises the genre consciousness of the early Christian authors; a genre that can be precisely defined by means of a literary-critical description in terms of the criteria of narrativity, fictionality, relation to reality, metaphor, appeal structure and co-/contextuality. From a hermeneutic perspective, this new approach consists of a conscious affirmation of a plurality of interpretations that is established by the texts themselves and that also guarantees the timeliness and liveliness of the interpretations in a variety of reading situations.